Clinical or Subclinical? Thalamocortical Synchrony Tips the Scale of Temporal Lobe Seizures - Olive Tambou Nzoutchoum; Jeanne T. Paz (Epilepsy Currents, 2026)
Thalamo-cortical synchrony shapes seizure expression in human temporal lobe epilepsy Aung T, Li J, Tumnark T, Belly C, Thomas J, Jaber K, Parikh P, Zafar M, Southwell D, Chauvel P, Frauscher B, Gonzalez-Martinez J. Nat Commun . Published online May 25, 2026. doi:10.1038/s41467-026-73053-9 In drug-resistant temporal lobe epilepsy (DR-TLE), some seizures are clinically symptomatic while others remain electrographic despite arising from the same seizure-onset zone (SOZ), suggesting that clinical expression reflects network dynamics beyond seizure origin. We examined whether thalamo-cortical network engagement differs between clinical seizure (CS) and non-CS (NCS). We analyzed 286 seizures from 62 DR-TLE patients recorded using stereoelectroencephalography with pulvinar and/or anterior thalamic group coverage. Thalamo-cortical synchrony during the first 20 s of seizure onset was quantified as correlation between stereoelectroencephalography-derived time-frequency patterns in thalamic nuclei and the cortical SOZ. Synchrony was significantly stronger during CS than NCS ( P < .0001, δ > 0.6), including within-subject analyses, and was independent of other clinical variables, including postsurgical outcome. Linear mixed-effects modeling identified seizure type as the sole independent predictor of synchrony ( P = .0069). These findings identify thalamo-cortical synchrony as a network-level feature associated with CS expression in DR-TLE.